2016
DOI: 10.1007/s40618-016-0592-8
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin potentiates transdifferentiation of bone marrow mesenchymal stem cells into the beta cells in vitro

Abstract: Quercetin has a strengthening effect on the differentiation of rat bone marrow mesenchymal stem cells into β-cells and increases insulin secretion from the differentiated β-cells in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…It enhanced the differentiation of BM-MSCs into bone cells in rat [129] and mice models [130]. In vitro, quercetin promoted the differentiation of BM-MSCs into β-cells with increased insulin secretion [131]. In a rat model of spinal injury, a combination therapy including quercetin and hUC-MSCs improved the neurological functional recovery, increased axonal preservation, promoted macrophage polarization, decreased the size of the cystic cavity, reduced the proinflammatory cytokines, and increased anti-inflammatory cytokines compared with hUC-MSCs alone [132].…”
Section: Past and Future Perspectivesmentioning
confidence: 94%
See 1 more Smart Citation
“…It enhanced the differentiation of BM-MSCs into bone cells in rat [129] and mice models [130]. In vitro, quercetin promoted the differentiation of BM-MSCs into β-cells with increased insulin secretion [131]. In a rat model of spinal injury, a combination therapy including quercetin and hUC-MSCs improved the neurological functional recovery, increased axonal preservation, promoted macrophage polarization, decreased the size of the cystic cavity, reduced the proinflammatory cytokines, and increased anti-inflammatory cytokines compared with hUC-MSCs alone [132].…”
Section: Past and Future Perspectivesmentioning
confidence: 94%
“…Apigenin and luteolin promoted human hematopoietic stem cell differentiation [141] and were confirmed safe for developing vertebrates in terms of neurobehavior [142]. [138] into bone cells Increased Rat BM-MSCs cultures [129], mice BM-MSC cultures [130] Decreased Human BM cell cultures [133] into β-cells Increased Rat BM-MSCs cultures [131] into hepatic cells Increased Human BM cell cultures [134] into fat tissue cells Increased Human BM cell cultures [133] Proinflammatory cytokines Decreased Rat model of spinal cord injury [132] Anti-inflammatory cytokines Increased Rat model of spinal cord injury [132] Angiogenic factor secretion Increased Rat BM-MSC cultures [135] BDNF secretion Increased Human embryonic NSCs culture [138] BDNF: Brain-derived neurotrophic factor, BM: Bone marrow, hHSC: Human hematopoietic stem cells, MSC: Mesenchymal stem cells, NSC: Neural stem cells, hPSCs: Human pluripotent stem cells.…”
Section: Past and Future Perspectivesmentioning
confidence: 97%
“…10 Quercetin (QCT) is a phytoestrogen belonging to the flavonoids family found in daily nutrition like onions. 11 Thus far, antitumoral, anti-inflammatory, and antioxidant activities of this compound have been suggested. 11,12 Most importantly, it is reported that QCT potentiates the antitumor effects of DOX in cancer cell lines and prevents its toxicity in nontargeted tissues.…”
Section: Introductionmentioning
confidence: 99%
“…11 Thus far, antitumoral, anti-inflammatory, and antioxidant activities of this compound have been suggested. 11,12 Most importantly, it is reported that QCT potentiates the antitumor effects of DOX in cancer cell lines and prevents its toxicity in nontargeted tissues. 11 Vitamin E (Vit.E) is one of the best known antioxidant compounds necessary for physiological maintenance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation